Transcriptional regulation of aldehyde dehydrogenase 1A1 gene by alternative spliced forms of nuclear factor Y in tumorigenic population of endometrial adenocarcinoma - Mamat, Suhana; Ikeda, Jun-Ichiro; Tian, Tian; Wang, Yi; Luo, Wenjuan; Aozasa, Katsuyuki; Morii, Eiichi (Sage Publications, 2011)
High activity of aldehyde dehydrogenase (ALDH) is characteristic of normal and cancerous stem cells. Recently, high ALDH expression was shown to be associated with poor prognosis in uterine endometrial adenocarcinoma. The population with high ALDH activity (ALDH-hi) was more invasive, anti-apoptotic, and tumorigenic than that with low activity (ALDH-lo). Here, the transcriptional regulation of ALDH1A1 gene, which is responsible for ALDH activity, was examined in endometrial adenocarcinoma. The promoter region of ALDH1A1 contained CCAAT and octamer binding motifs, and their mutation diminished promoter activity. Among CCAAT-recognizing transcription factors, nuclear factor YA (NFYA) was involved in ALDH1A1 transcription. Two alternatively spliced isoforms of NFYA (NFYA-long and NFYA-short) have been reported. The sorted ALDH-hi population of endometrial adenocarcinoma preferentially expressed NFYA-short, whereas ALDH-lo dominantly expressed NFYA-long. NFYA-short possessed higher transactivation ability than did NFYA-long. In addition, an additive effect of NFYA with Oct-1, which recognizes octamer binding motif, was observed in ALDH1A1 transactivation. These results indicate that the alternatively spliced isoforms of NFYA, in cooperation with Oct-1, play an important role in ALDH1A1 expression in endometrial adenocarcinoma.